2013
DOI: 10.1161/circimaging.112.000131
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Early Aortic Stiffening in Patients With Transposition of the Great Arteries After Arterial Switch Operation

Abstract: Background-The elastic function of the aorta in patients with transposition of the great arteries after arterial switch operation (ASO) is suspected to be important for long-term prognosis. ; P<0.01). Aortic distensibility correlated negatively with the aortic areas (P<0.01). Pulse wave velocity was higher in adults after ASO (5.0±1.0 versus 3.8±1.3 m/s; P<0.01). In contrast to controls pulse wave velocity and distensibility correlated with age in patients (P=0.04 to <0.01), LV mass was higher in patients (P=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 40 publications
8
41
0
Order By: Relevance
“…This relation was also disclosed in TGA after arterial switch. 5 In our case the subendocardial viability ratio or Buckberg index was normal (99 and 104 on 2 different acquisitions), which is in line with the observations of Murakami et al 2 in children. Nevertheless, this index may decrease with age and impact on left ventricular function and coronary perfusion as suggested by Murakami and Niwa.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This relation was also disclosed in TGA after arterial switch. 5 In our case the subendocardial viability ratio or Buckberg index was normal (99 and 104 on 2 different acquisitions), which is in line with the observations of Murakami et al 2 in children. Nevertheless, this index may decrease with age and impact on left ventricular function and coronary perfusion as suggested by Murakami and Niwa.…”
supporting
confidence: 92%
“…Indeed, aortopathy has been extensively described in TGA patients, whatever the surgical procedure performed (atrial or arterial switch operation). [2][3][4][5] We recently showed that distensibility of the ascending aorta was also impaired in TGA after atrial switch and associated with increase strain of the descending aorta, despite the fact that great arteries were not mobilized in this surgery. …”
mentioning
confidence: 99%
“…4 Other factors may also contribute to early left ventricular dysfunction after ASO, including hypoplastic left anterior descending coronary artery, decreased coronary blood flow reserve, perfusion defects, and altered myocardial architecture. 5 Coronary abnormalities may be found in asymptomatic subjects after ASO in 3% to 7% of the population.…”
Section: See Article By Shepard Et Almentioning
confidence: 99%
“…3 In addition, early aortic stiffening in patients after ASO has been recognized as a contributing factor to left atrial enlargement and left ventricular diastolic dysfunction. 4 Other factors may also contribute to early left ventricular dysfunction after ASO, including hypoplastic left anterior descending coronary artery, decreased coronary blood flow reserve, perfusion defects, and altered myocardial architecture. 5 Coronary abnormalities may be found in asymptomatic subjects after ASO in 3% to 7% of the population.…”
Section: See Article By Shepard Et Almentioning
confidence: 99%
“…We have read the article "Implications of Early Aortic Stiffening in Patients With Transposition of the Great Arteries After Arterial Switch Operation" by Voges et al, 1 with great interest. We congratulate the authors for this study.…”
Section: To the Editormentioning
confidence: 99%